Community economic development ultimately ensures social development - Mathbor, Golam M. (BRAC University, 2010)
Community Economic Development (CED), a North American perspective which focuses on creating employment, income maintenance, empowering powerless and poor people, business development, sharing ownership, and government involvement in local development, is one of the most suitable interventions for achieving social development. However, it is critical that this intervention be culturally specific to the target population. This article briefly reviews the history of CED, definition, the concept of community, economic and social objectives, capital development, and the principles of empowerment. The Link between Community Economic Development and the principle of empowerment is also made. Four dimensions of empowerment are discussed. They are: personal empowerment, educational empowerment, economic empowerment and political empowerment. It is expected that the review will be useful to students and teachers, policy-makers and practitioners interested in the social development field.